Frontiers of Industrial Relations (Relations industrielles / Industrial Relations, 1960)
The article reviews the book, "Frontiers of Industrial Relations," edited by Robert D. Gray. Selected Papers published in observance of the Twentieth Anniversary of the Industrial Relations Section, California Institute of Technology, Pasadena, California.